Association of Pharmacologic Treatment of Urgency Urinary Incontinence With Sleep Quality and Daytime Sleepiness. Issue 2 (February 2018) - Warsi, Qurratul A.; Huang, Alison J.; Hess, Rachel; Arya, Lily A.; Richter, Holly E.; Bradley, Catherine S.; Rogers, Rebecca G.; Myers, Deborah L.; Johnson, Karen C.; Winkelman, William D.; Gregory, W. Thomas; Kraus, Stephen R.; et al.
Abstract : OBJECTIVE: To evaluate the association between pharmacologic therapy for urgency urinary incontinence (UUI) and sleep quality. METHODS: We conducted a planned secondary data analysis of sleep outcomes in a previously conducted multicenter, double-blind, 12-week randomized trial of pharmacologic therapy for urgency-predominant incontinence among community-dwelling women self-diagnosed using the 3-Incontinence Questions questionnaire. Participants (N=645) were assigned randomly to 4–8 mg antimuscarinic therapy daily or placebo. At baseline and 12 weeks, participants completed a validated voiding diary to evaluate incontinence and voiding symptoms, the Pittsburgh Sleep Quality Index to evaluate sleep quality, and the Epworth Sleepiness Scale to evaluate daytime sleepiness. RESULTS: Mean (SD) age was 56 (±14) years, 68% were white, and 57% had poor sleep quality (Pittsburgh Sleep Quality Index score greater than 5). Mean frequency of any urinary incontinence and UUI was 4.6 and 3.9 episodes/d, respectively. After 12 weeks, women randomized to the antimuscarinic group reported greater decrease compared with the placebo group in UUI frequency (0.9 episodes/d; P <.001) and diurnal and nocturnal voiding frequency ( P <.05). As compared with the placebo group, women in the antimuscarinic group also reported greater improvement in sleep quality (total Pittsburgh Sleep Quality Index score 0.48; P =.02) with greater improvement in sleep duration and sleep efficiency subscales ( P <.05). The intervention did not affect daytime sleepiness. CONCLUSION: Pharmacologic treatment of UUI is associated with decreased incontinence frequency and nocturia and improvement in overall sleep quality, sleep duration, and sleep efficiency. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT00862745. Abstract : Pharmacologic treatment of urgency urinary incontinence is associated with improvement in overall quality of sleep, sleep duration, and sleep efficiency.